EFEKTIVITAS PENYEBARAN INFORMASI PUBLIK MELALUI INSTAGRAM OLEH DINAS KOMUNIKASI DAN INFORMATIKA KABUPATEN KARAWANG - , Syarif Abdilah; Hanny Purnamasari (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2024)
Since the turn of the century, mobile technology has enhanced online interactions, including in the field of governance. In Indonesia, the government's use of social media has become an important innovation in governance, enabling more direct public participation. This study aims to evaluate the effectiveness of Instagram use by the Karawang Regency Communication and Informatics Agency (Diskominfo) in improving public services. The research method used is a qualitative approach with a literature study from various sources, including government regulations, research journals, and books. Data was obtained from Instagram posts and the official website of Diskominfo Karawang, analyzed using the organizational effectiveness theory by Gibson, Ivancevich, Donnelly with dimensions of production, efficiency, satisfaction, adaptability, and development. The research results show that Diskominfo Karawang has regularly produced content, but interaction with the community still needs to be improved. The use of Instagram has helped in disseminating public service information and increasing transparency, although it has not been fully effective in engaging the community. In conclusion, while Instagram has enhanced communication and transparency, better strategies are needed to increase public participation and the effectiveness of public services. Measuring the utilization of social media is important to maximize its potential and benefits for better governance.